Perceived stress and self‐efficacy are associated with diabetes self‐management among adolescents with type 1 diabetes: A moderated mediation analysis. (6th October 2019) - Guo, Jia; Yang, Jundi; Wiley, James; Ou, Xiancai; Zhou, Zhiguang; Whittemore, Robin
Abstract: Aims: The aims of this study were to: (a) determine if self‐efficacy mediates the relationship between perceived stress and diabetes self‐management in adolescents with type 1 diabetes (T1D); and (b) explore whether perceived stress moderated the self‐efficacy and diabetes self‐management relationship. Design: Non‐experimental, descriptive correlational design, conducted from January–December 2016. Methods: Guided by the Adaptation to Diabetes framework, data on demographic and clinical characteristics, perceived stress, self‐efficacy and diabetes self‐management were collected. Descriptive analyses and regression analyses were generated by SPSS Version 22. Structural equation modelling was implemented with the MPlus program. Results: There was no direct effect of perceived stress on diabetes self‐management; however, self‐efficacy mediated the relationship between perceived stress and diabetes self‐management. Adolescents who had high self‐efficacy and low perceived stress demonstrated better diabetes care activities and diabetes communication than would be predicted from the main effects of self‐efficacy and perceived stress alone. Conclusions: Decreasing perceived stress and improving self‐efficacy are important strategies to improve diabetes self‐management in adolescents with T1D. Impact: Adolescents with T1D experience considerable stress with daily self‐management demands. This study highlights the mediating role of self‐efficacy on perceived stress and diabetes self‐management. Assessment of perceived stress and self‐efficacy in self‐management tasks in adolescents with T1D may help nurses individualize self‐management education and support. Incorporating strategies to promote stress management and self‐efficacy in diabetes education may also improve diabetes self‐management. Abstract : 目的: 本研究的目的是:(a)确定自我效能感是否调节在1型糖尿病(T1D)青少年的感知压力和糖尿病自我管理之间的关系;(b)探讨感知压力是否调节自我效能感和糖尿病自我管理关系。 设计: 2016年1月‐12月间实施的非实验性的描述性相关设计。 方法: 在糖尿病适应性框架的指导下, 收集了人口学和临床特征、感知压力、自我效能和糖尿病自我管理方面的数据。采用SPSS 22版本进行描述性分析和回归分析。利用MPlus程序进行结构方程建模。 结果: 感知压力对糖尿病自我管理没有直接影响;然而, 自我效能感调节了感知压力和糖尿病自我管理之间的关系。具有高自我效能感和低感知压力的青少年表现出更好的糖尿病护理活动和糖尿病沟通能力, 这是自我效能感和感知压力的主要影响所不能预测的。 结论: 减少感知压力和提高自我效能感是改善青少年T1D患者糖尿病自我管理的重要策略。 影响: 患有T1D的青少年在日常自我管理需求方面承受着相当大的压力。本研究强调了自我效能感在感知压力和糖尿病自我管理中的中介作用。评估青少年T1D患者的自我管理任务中的感知压力和自我效能感可以帮助护士赋予自我管理教育和支持个性化。在糖尿病教育中采用促进压力管理和自我效能感的策略也可以改善糖尿病自我管理。